PERANAN RUANG TERBUKA PUBLIK TERHADAP TINGKAT SOLIDARITAS DAN KEPEDULIAN PENGHUNI KAWASAN PERUMAHAN DI JAKARTA - Karya Widyawati; Atie Ernawati; Fanty Puspita Dewi (LPPM, 2011)
Less interaction between citizen caused of materialistic lifestyle impact the down of citizens’ solidarity and concertinity for their environment. According to Daldjoeni (1982:28), urbanization has replaced the primary relationship into secondary, which make the relationship between citizen was unstressed, mutual cooperation diminished and solidarity was lost. If this condition permitted, it will emerged many problems inside the community such as the security problems. Public open space in a region can be functioned as a center of orientation,an interaction tools and region identity which has interaction activity of the citizen culture. In fact, many public open space did not function optimally, sometimes even abandoned. It was getting worse by the lack of public open space as the impact of the converted urban infrastructures, which make the expectation for interaction between citizen was not realized. This research will be written in descriptive method which aim to discover how big is the role of public open space which is in descending quality and area to solidarity and concertinity of the inhabitant of many housing in some regions in Jakarta. The conclusion is that the existence of public open space which is in descending quality and area did impact to the descending of the solidarity and concertinity of citizens. To increase the solidarity and concertinity of the inhabitant of housing is by preparing good facilities of public open space,by increasing the quality of the public open space and also by doing the management with the base of the inhabitant of housing’s participants. Key Words : Public Open Space, Solidarity and Concertinity Rate, Inhabitant of Housing Region in Jakarta